2020
DOI: 10.1038/s41431-020-0691-z
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 gene variants may underlie interindividual variability and susceptibility to COVID-19 in the Italian population

Abstract: In December 2019, an initial cluster of interstitial bilateral pneumonia emerged in Wuhan, China. A human-to-human transmission was assumed and a previously unrecognized entity, termed coronavirus disease-19 (COVID-19) due to a novel coronavirus (SARS-CoV-2) was described. The infection has rapidly spread out all over the world and Italy has been the first European country experiencing the endemic wave with unexpected clinical severity in comparison with Asian countries. It has been shown that SARS-CoV-2 utili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
243
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(264 citation statements)
references
References 34 publications
8
243
0
2
Order By: Relevance
“…Notably, the total frequency of missense variants in the SEU population was the lowest (0.022), being more similar to the frequency in the East Asian population and Estonians ( Supplementary Table S6 and Figures 1C,D ). The low frequency of missense variants in the SEU population suggests that missense variants might play a protective role against COVID-19 infection (a similar hypothesis has been made by Benetti et al (2020) . Surprisingly, the differences between populations are reversed when considering missense variants predicted as deleterious by PROVEAN ( Choi and Chan, 2015 ), SIFT ( Ng and Henikoff, 2001 ), FATHMM ( Shihab et al, 2013 ), and PolyPhen2 ( Adzhubei et al, 2010 ; Supplementary Table S7 and Figure 1E ).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Notably, the total frequency of missense variants in the SEU population was the lowest (0.022), being more similar to the frequency in the East Asian population and Estonians ( Supplementary Table S6 and Figures 1C,D ). The low frequency of missense variants in the SEU population suggests that missense variants might play a protective role against COVID-19 infection (a similar hypothesis has been made by Benetti et al (2020) . Surprisingly, the differences between populations are reversed when considering missense variants predicted as deleterious by PROVEAN ( Choi and Chan, 2015 ), SIFT ( Ng and Henikoff, 2001 ), FATHMM ( Shihab et al, 2013 ), and PolyPhen2 ( Adzhubei et al, 2010 ; Supplementary Table S7 and Figure 1E ).…”
Section: Resultsmentioning
confidence: 62%
“…Furthermore, the first study ( Cao et al, 2020 ) did not discuss the ACE2 gene polymorphism in different European subpopulations. Recent whole-exome sequencing (WES)-based studies in such countries as Italy also aimed at the identification of the genetic COVID-19 susceptibility factors, with some missense ACE2 variants shown to have a protective role ( Benetti et al, 2020 ). The comprehensive study of the ACE2 variations focused on the possible protective pathogenic mutations revealed that missense mutations affecting protein interaction with S-protein exhibit overall low frequency due to the absence of natural selection with no discernable differences between populations ( Stawiski et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…We examined the variation in ACE2 binding residues within humans, some of which have been proposed to alter binding affinity ( 17 , 23 26 ). We integrated data from six different sources, dbSNP, 1KGP, Topmed, UK10K, gnomAD, and CHINAMAP, and identified a total of 11 variants in 10 of the 25 ACE2 binding residues ( Dataset S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Structural variations and different expression levels of the receptors and S protein priming proteases could potentially affect the spike/receptor interactions and subsequent spike cleavage e ciency which might cause differences of susceptibility of the host for the coronavirus infection capability and disease progression. A few studies in humans that investigated the ACE2 and TMPRSS2 genes reported variants segregating in different cohorts that might confer resistance against SARS-CoV-2 infection or modulate COVID-19 severity [ [48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological, biological and virological characteristics of coronaviruses, including their demonstrated ability to easily cross species barriers, suggest that pets and livestock should be considered as part of a global control and of a "One Health" approach to evaluate if animals that are close to human contacts could represent a risk source of infections for humans and vice versa [ [62][63]. Based on the mentioned preliminary evidences on the potential relationships between SARS-CoV-2 and pigs (even if contrasting) and considering i) the relevance of the pig production systems for meat supply, ii) that several other coronaviruses circulate in pigs and cause diseases in this livestock species [7][8]40 ], iii) that receptor variants may confer different susceptibility to infections within species [ [48][49][50][51][52][53], iv) that coronaviruses may jump the species barriers easily [ 5,18,46,57 ] and v) that variability of the RBD region of the spike protein might determine a quite large host spectrum for every coronaviruses [ 45,64 ], as part of a "One Health" approach [ 63 ], it is needed to evaluate the genetic variability segregating in pig populations potentially conferring differences of sensitivity to coronavirus-related diseases.…”
Section: Introductionmentioning
confidence: 99%